Práticas pedagógicas na educação infantil: a construção do sentido da escola para as crianças - Barros, Flávia Cristina Oliveira Murbach de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study, mainly, seeks to understand the meaning of scholarship for children between 4 and 5 years old, attending the last stage of Early Childhood Education. The work consisted of a bibliographical and field research involving, respectvely, three preschools located in the cities of São Carlos, Presidente Prudente and Assis. Our work has the theoretical support of the cultural-historical theory which comprehends humans and their development from their historical and social relations, the appropriation of objects of culture through human activity in specific times and places during their life course. It is assumed that the meanings that children‟s refer to school are linked to changes in pedagogical practices developed by educators which are conditioned to the culture of each school. The field research was divided into three stages: 1) observation of daily activities of one class in each school, 2) observing and accompaniment of data components of each school l (history, methodologies, pedagogical practices, internal relations between toddlers and infants, children and adults), 3) development and implementation of individual interviews and employment of complementary techniques such as drawing and drama performed with the children. Data analysis was taken from: empirical description (school routine and teaching practices) and theoretical description (the production of meaning by children and school culture). The findings have indicated that children see school as a place to learn, play and make friends. However, the differences relates among the schools are based on how mediations are made for the construction of meaning by children in s different schools cultures.

A pesquisa de Doutorado, que deu origem a esta tese, teve como objetivo principal compreender qual o sentido de escola que as crianças pequenas (última etapa da Educação Infantil – 4 e 5 anos ), que frequentam instituições escolares que utilizam práticas pedagógicas diferentes, atribuem a esses espaços. Os objetivos específicos se desmembraram em investigar como as crianças percebem a escola a partir do que vivenciam e a cultura escolar de cada escola pesquisada. Tem-se, como suporte teórico, a teoria histórico-cultural, que concebe o homem e seu desenvolvimento com base em suas relações histórico-sociais, pelas apropriações dos objetos da cultura por meio da atividade humana, em momentos e espaços específicos, durante sua trajetória de vida. A hipótese proposta é de que os sentidos atribuídos à escola pelas crianças estão atrelados às diferenças nas práticas pedagógicas desenvolvidas pelos professores, condicionadas à cultura de cada escola. O trabalho constituiu-se por pesquisa de campo, envolvendo três escolas de Educação Infantil, respectivamente, dos municípios paulistas de São Carlos, Presidente Prudente e Assis. A pesquisa de campo se dividiu em três momentos: 1) observação das atividades cotidianas de uma turma em cada escola; 2) acompanhamento e registro de dados componentes da cultura escolar de cada escola (histórico, metodologias, práticas pedagógicas, relações internas entre crianças e crianças, crianças e adultos); e 3) atividades de intervenção para a coleta de dados (entrevista individual, desenho e dramatização realizadas com as crianças). O tratamento dos dados foi realizado com base em: descrição empírica (cotidiano das escolas e práticas pedagógicas) e análise teórica (a produção de sentido pelas crianças e a cultura escolar). As constatações apontam que as crianças das escolas pesquisadas veem esse espaço como um...
Keywords: Educação de crianças; Escolas; Sentido (Filosofia); Cultura; Pratica de ensino; Schools